Dose-Response Reduction in Risk of Nasopharyngeal Carcinoma From Smoking Cessation: A Multicenter Case-Control Study in Hong Kong, China - Wang, Lijun; Mai, Zhi-Ming; Ngan, Roger Kai-Cheong; Ng, Wai-Tong; Lin, Jia-Huang; Kwong, Dora Lai-Wan; Chiang, Shing-Chun; Yuen, Kam-Tong; Ng, Alice Wan-Ying; Ip, Dennis Kai-Ming; Chan, Yap-Hang; Lee, Anne Wing-Mui; et al. (Frontiers in Oncology, 2021)
Background: Cigarette smoking is associated with nasopharyngeal cancer (NPC) risk. Whether quitting reduces the risk is unclear. We investigated the associations of NPC with duration of and age at quitting in an endemic region. Methods: We investigated the associations between NPC and quitting in a multicenter case-control study in Hong Kong with 676 newly diagnosed NPC cases and 1,285 hospital controls between 2014 and 2017, using a computer-assisted self-administered questionnaire. Multivariable unconditional logistic regression yielded adjusted odds ratios (AORs) of NPC by quitting status, duration and age of quitting, combinations of duration and age of quitting, and quitting to smoking duration ratio, compared with current smoking. Results: Quitting (AOR 0.72, 95% CI 0.53–0.98) and never smoking (0.73, 0.56–0.95) were associated with lower NPC risk. NPC risk decreased with (i) longer quitting duration (P < 0.01), reaching significance after 11–20 (0.62, 0.39‒0.99) and 20+ years (0.55, 0.32–0.93) of quitting; (ii) younger quitting age (P = 0.02), reaching significance for quitting at <25 years (0.49, 0.24–0.97); and (iii) higher quitting to smoking duration ratio (P < 0.01), reaching significance when the ratio reached 1 (0.60, 0.39‒0.93). Quitting younger (age <25) appeared to confer larger reductions (49% for ≤10 years of quitting, 50% for 11+ years) in NPC risk than quitting at older ages (25+) regardless of quitting duration (16% for ≤10 years, 39% for 11+ years). Conclusions: We have first shown longer duration and younger age of quitting were associated with lower NPC risk, with dose-response relations. Our findings support including smoking as a cause of NPC. Stronger tobacco control measures and quitting services are needed to prevent NPC.